Development and Testing of Instrument to Assess Preterm Infant Care Practice in Neonatal Care Units - Shrestha , Tumla; Bista, Archana Pandey (Europasian Journal of Medical Sciences, 2021)
Background: Preterm infants (PTIs) are vulnerable to morbidity, mortality, disability. They require special treatment and care in neonatal care units (NCUs) for survival and developmental potential. Nurses have the significant responsibility for providing quality care to these infants. To find out the care status, it is necessary to have a valid and reliable instrument. Objective: The study was conducted to develop and test an instrument to assess PTI care practice by nurses in NCUs. Methods: The instrument was developed based on literature review and the finding of the focus group discussion (FGD). The instrument was developed in August 2020 and pretested among 30 nurses working in NCUs of two private teaching hospitals of Kathmandu during September 2020. Measures were used to ensure the validity of the instrument. The content validity index (CVI) scores for items and scale were calculated from the scores given by the eight experts. The Cronbach alpha (α) was calculated considering the acceptable α-value > 0.7. Results: The instrument having four domains, 47 items and 5 sub-items was developed to assess PTI care practice. The instrument had a satisfactory CVI score for each item (>0.75) and overall scale (>0.9). The Cronbach alpha value for the subscales were between 0.79 and 0.88 and the overall scale was >0.93. Conclusion: The instrument to assess preterm infant care practice provided by nurses in NCU was developed with adequate theoretical and contextual background. Necessary validity and reliability processes and criteria were also employed. Therefore, the instrument might be useful to assess the PTI care practice of nurses in NCUs in Nepalese context. DOI: https://doi.org/10.46405/ejms.v3i2.260